Features of Application of the Optimized Physical Rehabilitation Program in Patients with Coronary Heart Disease - Vladymyrov, Oleksandr A.; Kurtian, Tetiana V.; Vladymyrova, Nataliia I.; Verych, Nataliia M.; Polyanska, Oksana S. (Ukrainian Journal of Cardiovascular Surgery, 2023)
Multisymptomatic coronary heart disease (CHD) remains a leading problem in cardiology. A person’s ability to perform physical work determines their quality of life, especially in patients with existing symptoms of damage to the cardiovascular system. The most advanced approach in the physical rehabilitation of patients with CHD is the use of ergometric testing indicators. The aim. To study the influence of the developed method of cycling training on the indicators of cardiopulmonary exercise (CPX) in patients with CHD. Materials and methods. We examined 65 men with CHD, I-II functional class stable angina pectoris, mean age 44.6 ± 1.39 years (from 32 to 60 years). The diagnosis was made on the basis of clinical findings, electrocardiography and laboratory examination according to the generally accepted criteria of the European Society of Cardiology. Results. The treatment results were evaluated two weeks after the completion of the physical rehabilitation program. Qualitative assessment was performed by using the CPX test with the recording of cardiac bioelectric potentials from 12 leads. The criteria for discontinuation of the test were generally accepted provisions based on WHO recommendations. While developing a physical rehabilitation program and predicting the timing of a functional recovery, several factors have to be taken into account that significantly affect the patient’s motor activity and determine the pace and outcome of the rehabilitation process as a whole. Long-term, regular physical activity in patients with CHD with limited coronary reserve have an impact on the mechanisms of cardiac function regulation, synchronization and optimization of the activity of the muscular, cardiovascular and respiratory systems. Systematic training sessions reduce the volume of drug therapy and can improve the patients’ quality of life. Conclusions. The use of the proposed individualized uniform interval cycling training combined with the intake of citrulline malate leads to a significant improvement in the achieved load capacity, heart rate, duration of work, total volume of completed work, inotropic reserve index, optimization of coronary blood circulation and improvement of bioenergy metabolism in the myocardium.